Analysis of Market Traders’ Adoption Behavior Using the Theory of Planned Behavior and the Technology Acceptance Model - Friedrich (Global Journal of Food and Agribusiness Management, 2024)
Although new or enhanced technology can be used to reduce high tomato losses in the fruit supply chain, adoption behavior is rarely known. The use of lining material to improve tomato packaging in Tanzania serves as an example of how socio-psychological factors impact traders' adoption behavior of new postharvest handling technology. This study is based on the Theory of Planned Behavior and the Technology Acceptance Model. According to the study's findings, respondents' behavioral intention was primarily explained by their subjective norm and perceived behavioral control. Perceived utility and perceived ease of use had a considerable impact on attitude, even if attitude was not a significant determining factor. Given that the structural transformation of emerging economies depends on the adoption of technology, our findings offer fresh perspectives on behavioral acceptance study in the relevant developing countries' tomato production sectors.